Analisis Kasus Kepailitan PT Metro Batavia : Tinjauan Terhadap Faktor Penyebab Dan Implikasinya Terhadap Praktik Manajemen Keuangan - Bonaraja Purba; Aisyah Ameilia; Cut Aliyyah; Iin Sintia (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
This analysis of the bankruptcy case of PT Metro Batavia aims to investigate the factors causing bankruptcy and their implications for the company's financial management practices. PT Metro Batavia, a large company in the transportation sector in Indonesia, experienced operational failure and eventually went bankrupt. Factors causing bankruptcy observed include ineffective financial management, unwise investment decisions, debt policies that are not managed properly, and lack of transparency in financial reporting. The implications of this bankruptcy can affect the company's financial management practices in the future. In this study, an in-depth analysis of the bankruptcy case of PT Metro Batavia was conducted to identify critical mistakes made by the company in managing their finances. In addition, this research also provides new insights about effective financial management practices and actions that should be avoided in managing company finances. This research can contribute to the literature on financial management and bankruptcy studies as well as being a reference for business practitioners, regulators and academics in formulating better strategies and policies to prevent corporate financial failures in the future